Procedure for selecting appropriate steels for machine design - Zorgani, Muftah Em. M (Cranfield University, 2010)
Selection of steels for industrial purposes usually means choosing a type of steel to make a part or a product. The steel that is chosen must meet all the designer requirements. A quantitative selection procedure has been used to analyze the large amount of data involved in this selection process so that a complete and systematic evaluation can be made. The designer is responsible for the selection of steel, and this selection requires the designer to find data and information on the mechanical properties required, and also learns ways to improve these properties through different heat treatment processes. When a large number of steels and a large number of specified mechanical properties are being evaluated for selection, the weighed properties method can require a large number of tedious and time-consuming calculations. In such cases a computer program could greatly facilitate the selection process. This thesis reports the selection of steels for gears, shafts, fasteners and springs where the steps involved in the weighted properties method which is written in the form of a simple computer program to select steels from a data bank. This program also includes the digital logic method to help in determining weighing factors. The steels are ranked according to standard designation; BS, AISI, and DIN. It has been found that alloyed steels hardened and tempered at 2050C are most suitable for gears, shafts, fasteners, and springs when higher mechanical properties required, and carbon and low alloyed steels when cost is the main consideration.
Keywords: Gears; shafts; fasteners; springs; performance index; relative importance